2017
DOI: 10.1109/lawp.2017.2768383
|View full text |Cite
|
Sign up to set email alerts
|

Highly Integrable Paper-Based Harmonic Transponder for Low-Power and Long-Range IoT Applications

Abstract: Abstract-In this letter, the design and performance analysis of a harmonic planar transponder on paper, which conjugates compactness and scalability, are presented. The tag, targeted for a fundamental frequency of 1.2 GHz, is based on a frequency doubler with a single lumped component (a low-barrier Schottky diode) and a system of nested tapered annular slot antennas. Both antennas, orthogonally placed, feature a maximum gain around 3 dBi. The frequency doubler is optimized for power levels in the order of −13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…where P f 0 avs is the available source power at f 0 , and P 2 f 0 load is the output harmonic power delivered to the load. To extend the read-out distance of the system, the frequency doubler is generally designed to have a low C l for low available input power (P f 0 avs < −20 dBm) [45], [46]. In the schematic in Fig.…”
Section: B Harmonic Backscatteringmentioning
confidence: 99%
See 2 more Smart Citations
“…where P f 0 avs is the available source power at f 0 , and P 2 f 0 load is the output harmonic power delivered to the load. To extend the read-out distance of the system, the frequency doubler is generally designed to have a low C l for low available input power (P f 0 avs < −20 dBm) [45], [46]. In the schematic in Fig.…”
Section: B Harmonic Backscatteringmentioning
confidence: 99%
“…11 [45]. The transponder is dual-layer, it is targeted for a fundamental frequency f 0 = 1.2 GHz, and it is manufactured on a paper substrate by a technology we called "copper adhesive laminate" (parameters of the equivalent composite substrate, including both paper and the glue layers interposed between each copper layer and paper: dielectric constant: r = 2.55, loss tangent: tan δ = 0.05, substrate thickness: h = 0.3 mm, trace conductivity: σ cu = 5.810 7 S/m), described in detail in [44].…”
Section: Harmonic Tags For Electronic Article Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…1) [18], [19]. Thanks to the frequency orthogonality between the launched and backscattered signals, the harmonic sensor system can remarkably suppress electromagnetic interferences, such as crosstalk and clutter [20], [21]. According to this principle, Huang et al have demonstrated a passive harmonic sensor for liquid sensing in healthcare applications.…”
Section: Introductionmentioning
confidence: 99%
“…reader sends a signal at the fundamental frequency f 0 to interrogate a tag that reflects and modulates a higher harmonic (e.g. : 2f 0 ) detectable by the reader [1]. The transponder, therefore, requires a dual-band antenna and a non-linear device, such as a diode.…”
Section: Introductionmentioning
confidence: 99%